Child survivors of the Holocaust in Greece : memory, testimony and subjectivity - Hantzaroula, Pothiti (Routledge studies in Second World War history, 2021)
Meaning, Memory and Archive: The Politics of the Creation of Archival Material on the Holocaust -- The War Became Real -- Trajectories of Escape from the German Persecution of the population of Salonika and Athens -- Hidden Children in Volos: Trajectories and Identities -- Life and Memory of Concentration Camps: The Bergen Belsen Experience -- The Beginning of an Unknown Era: The Role of anti-Semitism in the Construction of Postwar Identities -- Remaking the Meaning of Living Entre Mozotros: Postwar Reconstruction of Jewish Communities -- Family Legacies: Memory, Postmemory and Transgenerational Haunting -- The Legacy of the Holocaust and Beyond.